Karakteristik Ekstrak Kulit Biji Kakao (Theobroma cacao L.) sebagai Sumber Antioksidan pada Perlakuan Suhu dan Waktu Maserasi - Dewi, I Gusti Ayu Meia; Ganda Putra, G.P.; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 1 (2021): Maret, 2021)
Cocoa bean husk is a waste of cocoa processing that is large enough and has not been used optimally. Cocoa bean husk can be used as a natural antioxidant by extracting the polyphenol compounds. This research aim to find out the effect of temperature and maceration time on the of cocoa bean husk extracts as a source of antioxidants and to determine the best temperature and time of maceration to produce cocoa bean husk extract as a source of antioxidants. This experiment used a factorial randomized block design with two factors. The first factor was maceration temperature consisting of 30 ±2?C , 40 ±2?C , dan 50 ±2?C . The second factor was maceration time consisting of 24, 36 and 48 hours. The data was analysed by analysis of variant and continued with the Tukey test. The results showed that maceration temperature had a very significant effect, while maceration time had a significant effect on yield, total phenolic, and antioxidant capacity. whereas the interaction between treatments had no significant effect on yield, total phenolic, and antioxidant capacity. The best treatment to produce cocoa bean husk extract as a source of antioxidants is to use a maceration temperature of 50 ±2?C and a maceration time of 48 hours with a yield characteristic of 2,77 percent, a total phenolic value of 72,35 mg GAE / g, and a capacity antioxidants amounting to 17,45 mg GAEAC / g, Keywords : cocoa bean husk, extraction, polyphenol, antioxidant.